2023
DOI: 10.1021/acs.iecr.3c03817
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Discovery of Metal–Organic Frameworks for CO2 Capture by Artificial Intelligence

Hasan Can Gulbalkan,
Gokhan Onder Aksu,
Goktug Ercakir
et al.

Abstract: The existence of a very large number of porous materials is a great opportunity to develop innovative technologies for carbon dioxide (CO 2 ) capture to address the climate change problem. On the other hand, identifying the most promising adsorbent and membrane candidates using iterative experimental testing and brute-force computer simulations is very challenging due to the enormous number and variety of porous materials. Artificial intelligence (AI) has recently been integrated into molecular modeling of por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…It should be noted that having failed synthesis experiments for a particular MOF under various different synthesis conditions does not necessarily mean that the synthesis would be infeasible. In fact, some of the problems encountered in MOF synthesis could be solved through the use of artificial intelligence-driven techniques . For instance, it was recently shown that using a genetic algorithm optimization procedure, synthesis conditions that can lead to efficient and/or high-quality synthesis of HKUST-1 and Al-PMOF can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that having failed synthesis experiments for a particular MOF under various different synthesis conditions does not necessarily mean that the synthesis would be infeasible. In fact, some of the problems encountered in MOF synthesis could be solved through the use of artificial intelligence-driven techniques . For instance, it was recently shown that using a genetic algorithm optimization procedure, synthesis conditions that can lead to efficient and/or high-quality synthesis of HKUST-1 and Al-PMOF can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Many computational studies on MOF-based membranes serve as a starting point for listing promising membranes, though they rely on several assumptions [206][207][208][209][210][211][212][213]. Many studies use rigid frameworks to predict gas separation performance.…”
Section: Outlook and Challengesmentioning
confidence: 99%
“…Machine learning was successfully employed for exploring sustainability-focused reactions and design processes, such as the design of electrocatalysts for the CO 2 reduction, 54–56 the design of metal–organic frameworks to capture CO 2 , 2,57–59 helping to find greener solvent alternatives 60,61 and the synthesis methanol from CO 2 . 62…”
Section: Machine Learning and Ai And Their Impactmentioning
confidence: 99%
“…The success of such methods has already extensively showcased their potential, 1–3 also directly tackling CO 2 conversion 4–8 and storage. However, even when directly addressing climate change-related issues, scientists often overlook the environmental consequences of their direct actions; their research efforts have an associated environmental cost.…”
Section: Introductionmentioning
confidence: 99%